Nonlinear analysis of vehicle control actuations based on controlled invariant sets - Németh, Balázs; Gáspár, Péter; Péni, Tamás (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, an analysis method is applied to the lateral stabilization problem of vehicle systems. The aim is to find the largest state-space region in which the lateral stability of the vehicle can be guaranteed by the peak-bounded control input. In the analysis, the nonlinear polynomial sum-of-squares programming method is applied. A practical computation technique is developed to calculate the maximum controlled invariant set of the system.
Keywords: vehicle dynamics; sum-of-squares programming; Lyapunov methods